2007
DOI: 10.1021/es063102j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cd(II), Cu(II), and Pb(II) Biouptake by Green Algae in the Presence of Humic Acid

Abstract: The present study examines the role of humic acid, as a representative of dissolved organic matter, in Cd(II), Cu-(II), and Pb(II) speciation and biouptake by green microalgae. Cellular and intracellular metal fractions were compared in the presence of citric and humic acids. The results demonstrated that Cd and Cu uptake in the presence of 10 mg L -1 humic acid was consistent with that predicted from measured free metal concentrations, while Pb biouptake was higher. By comparing Cd, Cu, and Pb cellular concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 33 publications
8
46
1
1
Order By: Relevance
“…The latter assumption is not so unrealistic given the linear increase of the amount of FA and HA adsorbed to algal surface with bulk concentration of humic substances in the range from 1 to 15 mg C L −1 . [12,16] Pb uptake in the presence of DOM of variable compositions Experimental results confirmed that individual DOM components or their mixtures significantly reduced internalised Pb, used as a measure of Pb uptake by Chlorella kesslerii in comparison with a system that contained no DOM (Fig. 3).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The latter assumption is not so unrealistic given the linear increase of the amount of FA and HA adsorbed to algal surface with bulk concentration of humic substances in the range from 1 to 15 mg C L −1 . [12,16] Pb uptake in the presence of DOM of variable compositions Experimental results confirmed that individual DOM components or their mixtures significantly reduced internalised Pb, used as a measure of Pb uptake by Chlorella kesslerii in comparison with a system that contained no DOM (Fig. 3).…”
Section: Resultssupporting
confidence: 57%
“…The enhanced Pb uptake observed in the presence of DOM of different compositions is in qualitative agreement with DOM sorption to algae. Hence, it was previously proposed [12] that the binding of DOM to algae increased the number of binding sites (e.g. carboxylic groups) on the algal surface available for Pb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the adsorbed humic substances might affect the properties of the algal surface by enhancing membrane permeability of both lipophilic metal complexes (24) and hydrophilic substances (25), by increasing the negative surface charge (6,11), and by adding the additional binding sites (10,11,26).…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the proportion of metal bound to algae and metal bound to humic substance bound to algae the ternary complex was suggested to contribute (e.g., for Pb) or not (e.g., for Cd and Cu) to the overall cellular metal (7,10). However, the above considerations were developed at constant accumulation times, assuming that the equilibrium is attained between the algal surface and the medium.…”
Section: Introductionmentioning
confidence: 99%